Analisis Penyimpanan Makanan dalam Program Makan Bergizi Gratis (MBG) Dari Risiko Keracunan Pangan di SMPN 07 Seluma Provinsi Bengkulu - Gazali; Meisica Melani Putri Amanda (Jurnal Sanitasi Profesional Indonesia, 2026)
The Free Nutritious Meal Program (MBG) is a strategic government program for fulfilling the nutritional needs of students through the provision of safe and suitable food. The success of this program is strongly influenced by food safety management, particularly the duration of food storage from the time it is cooked until it is consumed. Food stored for too long at room temperature, within the danger zone of 5–60°C, allows pathogenic bacteria such as Staphylococcus aureus, Salmonella sp., Escherichia coli, and Bacillus cereus to multiply rapidly, thereby increasing the risk of food poisoning. Several mass poisoning incidents during MBG implementation in various regions of Indonesia indicate that sanitation control and food handling remain serious concerns. This study aimed to analyze the duration of food storage, the sanitation of storage areas, food handling practices, food container conditions, and the risk of food poisoning in the MBG Program at SPPG Cahaya Negeri and SMPN 07 Seluma, Bengkulu Province. This descriptive study used a direct observation method with a checklist sheet over 10 days in April 2026. The observed variables included food storage duration, storage sanitation, food handling practices, container conditions, and food poisoning risk, observed from the time food was cooked at the SPPG until it was received and consumed by students. Data were analyzed univariately to describe the frequency distribution of each variable. The results showed that food storage duration was mostly in the moderately risky category (50%), storage sanitation was mostly good (90%), food handling practices were mostly non-compliant with standards (70%), food containers were mostly suitable (70%), and the overall food poisoning risk was mostly low (80%). Food storage duration that exceeds the safe limit, combined with non-compliant handling practices, has the potential to increase the risk of food poisoning, although good sanitation and suitable containers help to suppress this risk. Accelerating food distribution, improving food handling hygiene, and conducting regular monitoring of containers and sanitation are necessary to ensure food safety in the MBG Program.